EFFECT OF AGE AND PARITY ON PREGNANT WOMEN'S KNOWLEDGE ABOUT DISCOMFORT OF THE THIRD TRIMESTER - Maryati, Sri; Yanti, Damai (jfpublisher, 2022)
Introduction. Pregnancy is a physiological process that almost always takes place in every woman. However, there are some mothers who experience discomfort. Knowledge can be influenced by a person's characteristics including age and parity. Increasing a person's age can affect the increase in knowledge gained. Likewise, mothers who have several children generally have better knowledge because they have had hands-on experience in previous pregnancies. The incidence of discomfort in the third trimester at Clinic A was 56 cases. The purpose of this study was to determine the effect of age and parity on knowledge of pregnant women about discomfort of the third trimester at Kilink